GENDERED PERSPECTIVES IN TRANSLATION: A CRITICAL DISCOURSE ANALYSIS OF MANTO’S ‘THANDA GOSHT’ IN ENGLISH (Contemporary Journal of Social Science Review, 2025)
This study examines the impact of translator gender on the translation process, exploring how gender influences the meaning and interpretation of translated texts. Focusing on Sa’adat Hassan Manto’s short story “Thanda Gosht,” this research compares two translations: one by Mustansar Dalvi, an Indian translator, and another by C. Christine Fair, an American translator. The study reveals that translators’ gender can significantly influence the translation outcome, leading to potential misinterpretations and altered meanings. Employing a Critical Discourse Analysis (CDA) approach combined with a constructivist paradigm, this research investigates the intersection of translators’ gender, subjectivity, and translation strategies, finding that the gender of the translator significantly affects the translation outcome. This study emphasises the importance of considering translators’ gender in the process of translation and highlights the need for translators to be aware of their subjective biases and cultural backgrounds.